2021
DOI: 10.1038/s41598-021-94880-4
|View full text |Cite
|
Sign up to set email alerts
|

Human beta defensin levels and vaginal microbiome composition in post-menopausal women diagnosed with lichen sclerosus

Abstract: Human beta defensins (hBDs) may play an important role in the progression of lichen sclerosus (LS), due to their ability to induce excessive stimulation of extracellular matrix synthesis and fibroblast activation. The genetic ability of the individual to produce defensins, the presence of microbes influencing defensin production, and the sensitivity of microbes to defensins together regulate the formation of an ever-changing balance between defensin levels and microbiome composition. We investigated the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Overproduction of defensins translate into increased activation of fibroblasts and synthesis of the extracellular matrix, which promotes disease progression. This suggests the possibility of treating such conditions by modulating the composition of the microbiome contributing to this condition [ 115 ].…”
Section: Hbd-2 In Pregnancy and Infancymentioning
confidence: 99%
“…Overproduction of defensins translate into increased activation of fibroblasts and synthesis of the extracellular matrix, which promotes disease progression. This suggests the possibility of treating such conditions by modulating the composition of the microbiome contributing to this condition [ 115 ].…”
Section: Hbd-2 In Pregnancy and Infancymentioning
confidence: 99%
“…Several recent studies have demonstrated an association between low levels of β-defensin-2 and numerous obstetric and gynecologic pathologies, including preterm birth, bacterial vaginosis, lichen sclerosis, sexually transmitted infections. 3,12,28,29 In regards to GBS specifically, prior in vitro work by Castro-Leyva et al demonstrated that when incubated with S. agalactiae, choriodecidual cells increased production of β-defensin-2. 30 Boldenow et al showed increased β-defensin-2 production by GBS-exposed amnion cells and also found that in bacterial culture, β-defensin-2 decreased GBS viability in a concentration-dependent manner.…”
Section: Results In the Setting Of What Is Knownmentioning
confidence: 99%
“…Microorganisms and inducible defensins mutually affect each other’s presence in the bladder; the resulting balance may also be affected by a number of external factors. Examination of HBD2 or HBD3 levels individually showed no association with microbial composition, but the combined effect of HBD2 and HBD3 [ 41 ] shows an increasingly pronounced difference in the abundance of the genera characteristic for the PH and BC groups; i.e., the higher the HBD2 and 3 levels, the greater the differences in the microbiome composition between the two groups. HBD3 is also bactericidal against some Gram-positive species, in addition to its ability to kill Gram-negative bacteria, which is also characteristic of HBD1–2 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%